Perforated isolated jejunal diverticulum: a rare cause of acute abdomen - Jha, Abhijeet; Ghuliani, Deepak; Jain, Sudhir K.; Ansari, Faiz M. (International Surgery Journal, 2019)
A 45-year-old female presented with pain in peri-umbilical region for past one day along with history of non-bilious vomiting and non passage of stool and flatus for past one day. On physical examination, patient was afebrile, mild dehydration was present, tachycardia of 102 beats per minute with normal blood pressure. On clinical examination, the abdomen was diffusely tender with rebound tenderness. Bowel sounds were absent. Laboratory investigations revealed leucocytosis. An erect plain chest X-ray was done, didn’t reveal any gas under the diaphragm. Contrast enhanced computed tomography abdomen was done which showed a hollow viscus perforation with intra-abdominal free air and pelvic free fluid. Patient was resuscitated with IV fluid, broad-spectrum antibiotics were started and immediately taken up for exploratory laparotomy. Three jejunal diverticula identified at mesenteric border, with pin-head perforation in one of the diverticula. Small bowel resection including the three diverticula and primary end-to-end anastomosis was performed. Post-operative period was uneventful. Patient discharged on satisfactory conditions. This case stresses the importance to consider this entity in cases of unexplained gastrointestinal symptoms because any treatment delay may lead to unsuccessful clinical outcome.